INVENTARISASI ORDO DECAPODA DI PULAU PISANG PESISIR BARAT UNTUK PENYUSUNAN POSTER PEMBELAJARAN DI SEKOLAH MATERI KEANEKARAGAMAN HAYATI 1 - Indah Meika Sari; Widya Sartika Sulistiani; Rasuane Noor (EDUBIOLOCK, 2020)
Pisang Island is an island in the region of Pesisir Barat Regency, Lampung Province. Pisang Island has a land area of 148.82 Ha. The WestCoast Government plans that Pisang Island be made one of the touristdestinations on the West Coast. Of course, an area that is transitioning to atourist destination will have an influence on the ecosystem at sea. So beforethere was a transition to a tourist attraction, a research was carried out onPisang Island regarding the inventory of the Decapoda Order on PisangIsland. The objectives of the research concerning the Inventory of theDecapoda Order on Pisang Island in Pesisir Barat are: (1) Knowing thediversity of the Decapoda Order in Pisang Island. (2) Determine speciesdifferences between stations. (3) Knowing the research design being studiedcan be used as a poster. This type of research is descriptive qualitativeresearch, where this research was conducted directly on the Pisang Island,this research was conducted by recording as much as possible about theOrder. Analysis of data from the existing Decapoda Order and obtained fromthe results of the research at each station, the diversity index and itsdominance index were calculated.The results of research on Decapoda in Pisang Island, Pesisir BaratRegency, Lampung Province obtained data that found 4 species grouped in theCrustacean class. Species found on Pisang Island in the Decapoda Order werepredicted by Sesarmoides jacobsoni (Ihle, 1912), predicted by Zosimus aeneus(Linnaeus, 1758), predicted by Scylla serrata (Forskal, 1775), and predicted byMetapenaeus ensis (De Haan, 1844). Species differences between stationsnamely station one and station two were found species of white crabs(Sesarmoides jacobsoni) and mangrove crabs (Scylla serrata). Station threefound species of white crab (Sesarmoides jacobsoni), Crab crab (Zosimusaeneus), and Shrimp Donggol (Metapenaeus ensis). The results of postervalidation that have been developed in terms of design experts and materialexperts are getting a percentage of 85.6% with the criteria "Very Good".Validation was carried out by 2 Lecturers of Muhammadiyah Metro Universityconsisting of 1 Lecturer validating the design on the poster, while 1 Lecturervalidating the material on the poster. The results of the validation can beconcluded with the percentage that has been obtained stating that the poster isdeclared "Very Valid" and can be used.